Recent advances in surgical management of urinary incontinence - Downey, Alison (F1000Res, 2019)
There have been several recent developments in surgical treatments for male and female incontinence. This article reviews the current options for treatments of urge and stress incontinence in men and women. Treatments for urge incontinence discussed include intradetrusor onabotulinum toxin A, sacral neuromodulation and percutaneous tibial nerve stimulation. For stress incontinence, suburethral mesh, bulking agents, autologous slings, colposuspension, male slings and artificial urinary sphincters are assessed.